Studies of the performance of an IACT system for the TAIGA array - Kunnas, Maike Helena (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
The gamma rays emitted by cosmic accelerators are the most important messenger for astrophysics at the highest energies, and the Cherenkov radiation from the cascades they cause in Earth's atmosphere is a reliable way to detect them. One of the newest experiments for such earth-bound observation is the TAIGA experiment. This thesis investigates the performance of a possible air Cherenkov telescope system for the TAIGA experiment. The main principle of the TAIGA experiment is a combination between imaging air Cherenkov telescopes and Cherenkov shower front sampling stations. The point spread function of the intended telescope design has been determined with the Monte Carlo (MC)method and compared to a semi-analytic prediction. The mirror tiles to be installed into the prototype telescope at the TAIGA site have been characterized and an estimate of mirror alignment precision is given. The effective area of a single telescope, as well as of a 3-by-3 telescope array, were calculated and a method to reconstruct the shower energy from the image size is presented. In addition, the gamma hadron separation power of the telescopes in this setup via the "scaled image width" method has been determined using numerical simulations. It has been noticed that for core distances above 300 m the perceived image width stays constant. This effect is subsequently called the "Tur Tur" effect and been found to be a consequence of an increase of the average off-axis distance of the Cherenkov photon emission point for larger observation core distance. As an additional parameter, the possible influence of the earth's magnetic field on the image width has been studied. The impact of the pixel size of the camera on the image width has been studied using Monte Carlo simulations and a method of time-saving simulations for larger pixels exploiting the results for smaller has been developed. It has to be noted, however, that this method has been deemed deficient as the rejection of incomplete pixels lead to partial rejection of the actual ...